2019
DOI: 10.3892/etm.2019.8391
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective mechanisms of S-allyl-L-cysteine in neurological disease (Review)

Abstract: S-allyl-L-cysteine (SAC) is a sulfur-containing amino acid present in garlic and exhibits a wide range of biological activities such as antioxidant, anti-inflammatory, and anticancer agent. An earlier study demonstrated that SAC ameliorates oxidative damage in a model of experimental stroke. However, the antioxidant property of SAC does not suffice to explain its beneficial effects in terms of the underlying mechanisms. Endoplasmic reticulum (ER) stress and ER stress-induced cell death have been shown to be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Through an Nrf2‐dependent antioxidant response component, SAC has been shown to exhibit neuroprotective effects in ischemic nerve injury, retinal protection against kainate neurotoxicity, protection of dopamine neurons from the toxic effects of 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP), and repair of β‐amyloid‐induced brain damage (Kosuge, 2019; Zarezadeh et al., 2017). A master transcription factor that regulates phase 2 enzyme production, Nrf2, is inactive under normal settings because it binds to Kelch‐like ECH‐associated protein 1 (KEAP1).…”
Section: Bioactivities Of S‐allyl Cysteine (Sac)mentioning
confidence: 99%
“…Through an Nrf2‐dependent antioxidant response component, SAC has been shown to exhibit neuroprotective effects in ischemic nerve injury, retinal protection against kainate neurotoxicity, protection of dopamine neurons from the toxic effects of 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP), and repair of β‐amyloid‐induced brain damage (Kosuge, 2019; Zarezadeh et al., 2017). A master transcription factor that regulates phase 2 enzyme production, Nrf2, is inactive under normal settings because it binds to Kelch‐like ECH‐associated protein 1 (KEAP1).…”
Section: Bioactivities Of S‐allyl Cysteine (Sac)mentioning
confidence: 99%
“…Interestingly, several previous reports have documented a wide range of activities of garlic and its components, particularly SMC, for treatment of various physiological and pathological conditions [ 24 , 25 , 26 ]. In this regard, some previous reports revealed that garlic, SMC, and other organosulfur compounds of raw or extracted garlic showed anticancer [ 27 ], antioxidant [ 28 ], anti-inflammatory [ 29 ], antidiabetic [ 30 ], cardioprotective [ 24 ], neuroprotective [ 31 ], hypocholesterolemic [ 30 ], antiinfective [ 32 , 33 ], and hepatoprotective effects [ 34 , 35 , 36 ]. To the authors’ knowledge, no former investigations assessed the effect of SMC against C. parvum either in vitro or in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Active component N-α-[1-deoxy-D-fructos-1-yl]-L-arginine [FruArg] from AGE alleviated neuroinflammation by inhibiting the production of NO and regulating the expression of multiple protein targets related to oxidative stress in lipopolysaccharide activated murine BV-2 microglial cells [130]. S-allyl-L-cysteine [SAC] exerts significant protective effects against endoplasmic reticulum stress-induced neurotoxicity in cultured rat hippocampal neurons and organotypic hippocampal slice cultures [131]. SAC and FruArg are prototype for developing novel therapeutic drugs for neurological diseases.…”
Section: Neuroprotectionmentioning
confidence: 99%